Influence of women's autonomy on infant mortality in Nepal - Adhikari Ramesh; Sawangdee Yothin (BMC, 2011)
Abstract Background Nepalese women lag behind men in many areas, such as educational attainment, participation in decision-making and health service utilization, all of which have an impact on reproductive health outcomes. This paper aims to examine the factors influencing infant mortality, specifically, whether women's autonomy has an impact on infant mortality in the Nepali context. Methods Data were drawn from the Nepal Demographic and Health Survey, 2006. The analysis is confined to 5,545 children who were born within the five years preceding the survey. Association between infant mortality and the explanatory variables was assessed using bivariate analysis. Variables were then re-examined in multivariate analysis to assess the net effect of women's autonomy on infant mortality after controlling for other variables. Results The infant mortality rate (IMR) in the five years preceding the survey was 48 deaths per one thousand live births. Infant mortality rate was high among illiterate women (56 per 1000 live births) and among those not involved in decision making for health care (54 per 1000 live births). Furthermore, infant mortality was high among those women who had more children than their comparison group, who had birth intervals of less than two years, who had multiple births, who were from rural areas, who were poor, whose source of water was the river or unprotected sources, and who did not have a toilet facility in their household. Results from logistic regression show that women's autonomy plays a major role in infant mortality after controlling other variables, such as mother's sociodemographic characteristics, children's characteristics and other household characteristics. Children from literate women had a 32 percent lower chance (OR = 0.68) of experiencing infant mortality than did children from illiterate women. Furthermore, infants of women who were involved in decision-making regarding their own health care had a 25 percent lower (OR = 0.75) chance of dying than did infants whose mothers who were not involved in healthcare decisions. Conclusion Infant mortality is high in Nepal. In this context, mother's literacy and involvement in healthcare decision making appear to be the most powerful predictors for reducing infant mortality. Hence, in order to reduce infant mortality further, ongoing female education should be sustained and expanded to include all women so that the millennium development goals for the year 2015 can be attained. In addition, programs should focus on increasing women's autonomy so that infant mortality will decrease and the overall well being of the family can be maintained and enhanced.